2016
DOI: 10.1021/acs.biomac.6b01618
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Synthesis of Amino Acid Functional Polymers without Protection Group Chemistry

Abstract: The copolymerization of N-isopropylacrylamide (NiPAm) with aldehyde functional monomers facilitates postpolymerization functionalization with amino acids via reductive amination, negating the need for protecting groups. In reductive amination, the imine formed from the condensation reaction between an amine and an aldehyde is reduced to an amine. In this work, we categorize amino acids into four classes based on the functionality of their side chains (acidic, polar neutral, neutral, and basic) and use their am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“… 27 Despite all of these features, the use of poly(hydrazide)s as a reactive scaffold had been limited to the preparation of glycopolymers, 29 , 31 and for pH-responsive drug delivery. 32 36 Alternative elegant strategies using poly(alkoxyamine)s 37 , 38 and poly(aldehyde)s 39 41 have also been explored.…”
Section: Introductionmentioning
confidence: 99%
“… 27 Despite all of these features, the use of poly(hydrazide)s as a reactive scaffold had been limited to the preparation of glycopolymers, 29 , 31 and for pH-responsive drug delivery. 32 36 Alternative elegant strategies using poly(alkoxyamine)s 37 , 38 and poly(aldehyde)s 39 41 have also been explored.…”
Section: Introductionmentioning
confidence: 99%
“…We have reported the development of dynamic covalent polymers combined with hydrophobic forces to produce a range of switchable amino acid copolymers. PNIPAM copolymers where polymerized with an aldehyde functional comonomer and amino acid were conjugated onto the polymers forming dynamic copolymers with tunable temperature responsive properties and dynamic and bioinspired functionalities . We furthered this approach (development of carbonyl functional polymers) to produce doubly dynamic 3D‐printable macroporous cryogels, this time combining oxime chemistry and hydrogen bonding ( Figure ) .…”
Section: Polymers With Multi‐dynamic Covalent and Non‐covalent Interamentioning
confidence: 99%
“…Recently, Brisson et al reported the conjugation of amino acids to polymers with aldehyde groups in the side chain (Figure 26). [139,140] In a first step, a Schiff base was formed between the amine group and the aldehyde using acetic acid as the reaction solvent. Then, this reversible covalent bond was reduced with the aid of sodium borohydride, yielding irreversible bound histidine moieties in the polymer side chain.…”
Section: Conjugation Via Amine Functionalitiesmentioning
confidence: 99%